Facilitating cells: role in inducing transplantation tolerance. Issue 5 (October 2018) - Chhabra, Anita Yogendra; Ildstad, Suzanne T.
Abstract : Purpose of review: This review discusses the role and mechanisms by which facilitating cells promote stem cell engraftment and induce tolerance in HLA-disparate kidney transplant recipients. Recent finding: Facilitating cells in both mice and human are heterogeneous, consisting of several subpopulations. They have been shown to enhance stem cell engraftment in allogeneic recipients. They also increase hematopoietic stem cells (HSC) clonogenicity, enhance migration and homing of stem cells via secretion of cytokines/chemokines/growth factors, prevent apoptosis of stem cells and induce regulatory cells. This review summarizes the findings that led to the development of chimerism-based induction of tolerance using FCRx (a mobilized blood product enriched in stem cells and facilitating cells) in allogenic kidney transplant patients. Summary: A phase-2 clinical trial based on FCRx therapy has been successful in inducing tolerance to living donor kidney allografts, leading to withdrawal of immunosuppression in over 70% of patients transplanted. The ultimate goal of establishing tolerance in the absence of immunosuppresive drugs can be achieved using FCRx therapy.